FLC-based Renewable Wind Energy Viability Assessment in Central Luzon Philippines - Caldo, Rionel Belen (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
In this paper, the proponent designed and developed a fuzzy logic based control system for renewable wind energy viability analysis specifically in six selected sites in Central Luzon Philippines. The membership functions (MFs) were constructed for three classified parameters: wind resource density, other wind resource parameters and site-related criteria with 5%, 5% and 90% factor rates. The quantitative site assessment made by Karen Conover of Global Energy Concepts (GECs) was used for constructing the MFs and for establishing the 216 fuzzy rules using Sugeno-style of fuzzy inference system. The average score of selected sites were used for fuzzy logic assessment and it was realized that Sual Pangasinan and Carranglan Nueva Ecija are best suited for possible wind farm development considering that the linguistic assessment was “Very Good” while the rest were just “Good”. The results obtained using fuzzy logic and the reviewed literature was compared and a favourable correlation was observed. This means that the FLC-based wind viability assessment could be used as an effective computational tool for Central Luzon and even for other wind energy viability assessments inside and outside the country.